Conflict resolution an integrated approach to its styles, strategies and applications - Hashi, Abdurezak Abdulahi (Darul Tashih Enterprise, 2024)
This book, Conflict Resolution: An integrated Approach to its Styles, Strategies and Applications, uses analytical and comparative methods and addresses conflicts resolution, its concepts, functions and styles. It provides an academic readings of this field that is integrative and multidisciplinary in nature. Besides the concept, nature, theories, approaches, styles and steps of conflict resolution, the book also covers discussions related to the the Islamic perspective of conflict resolution. It offers a concise purview on the means and ways of resolving conflicts through and within the Somali history and tradition.